Preparation of Ligand‐Targeted Drug Conjugates for Cancer Therapy and Their Evaluation In Vitro. Issue 4 (13th September 2018) - Krishnan, Mena Asha; Sengupta, Sagnik; Chelvam, Venkatesh
Abstract: Present treatment strategies focus on minimizing unwanted toxicity to healthy cells during chemotherapeutic treatment. This is achieved by developing strategies to selectively deliver drugs to malignant cells over‐expressing specific protein biomarkers. The drugs are attached via a self‐immolative linker to a small molecule homing ligand having affinity for protein biomarkers over‐expressed during disease states. Several such targeting‐ligand drug conjugates have now reached preclinical and clinical trials, and this article aims to show a general methodology to prepare the same. Using solid‐phase peptide synthesis (SPPS) methodology, the targeting ligand is covalently linked to a peptide spacer having appropriate hydrophobic and hydrophilic amino acids. The targeting ligand–attached peptide spacer is next conjugated with the required drug molecule through a cleavable disulfide bond in a solution‐phase reaction. This protocol further elucidates the step‐by‐step procedures to be followed for complete evaluation of newly synthesized ligand‐targeted drug conjugates in vitro . © 2018 by John Wiley & Sons, Inc.